THE CONDUCT OF THE HAJJ AND ITS SOCIAL IMPACT ON THE MUSLIM COMMUNITY IN MALAYSIA 1975-2005 - Sharifah Binti Ismail (Journal of Islamic, Social, Economics and Development, 2020)
Hajj, the Muslim pilgrimage is the final pillar of Islam. The close association between hajj and the Malays as well as its status as a prominent religious foundation gives hajj a significant position in the society. Due to its religious significance and its unique position in the life of the Malays, the hajj has been a great interest to the Malaysian government and thus the government and its national hajj organization, Lembaga Tabung Haji (Tabung Haji) continuously undertakes a major role in the progress of the hajj institution in this country. Tabung Haji laid for the foundation and development of Malaysian hajj management. With the progress made in the pilgrimage management particularly during the period of 1975-2005, the hajj institution under the direction of Tabung Haji has experienced rapid expansion and reforms thus had direct social implications on the pilgrims and the hajj institution itself. Therefore, this paper examines the hajj institution in Malaysia under the administration of Tabung Haji. It also highlights the conduct of hajj from Malaysia with special reference to the roles of Tabung Haji and the hajj itself that have resulted in very important social consequences for all aspects of the pilgrims and pilgrimage. The researcher adopts a qualitative method that enables her to analyze and assess the material and information collected from the primary and secondary sources, interviews and personal observations. This study concluded that the period of 1975-2005 marked as a new transition era of the hajj institution in Malaysia into a more organized and modern hajj institution under the administration of Tabung Haji. The roles of Tabung Haji had considerably contributed to the significant changes in Malaysian hajj institution and led to transformative impacts on the conduct of hajj and on various social aspects of the Malaysian Muslim community life.